Available prognostic models for risk stratification of diffuse large B cell lymphoma patients: a systematic review. (January 2019) - Jelicic, Jelena; Larsen, Thomas Stauffer; Maksimovic, Milos; Trajkovic, Goran
Highlights: The IPI has been used for risk stratification in DLBCL for 25 years. Based on new knowledge on the pathobiology of DLBCL, a number of new prognostic models has been described. Most of the proposed prognostic models lack both external and internal validation. The IPI, R-IPI, and NCCN-IPI are the most studied prognostic models in DLBCL. Further studies combining biological and clinical markers are needed to determine the optimal prognostic tool in DLBCL. Abstract: The International Prognostic Index (IPI) has been used for risk stratification for a long time in diffuse large B cell lymphoma (DLBCL). Based on new clinical and biological prognostic markers, many new prognostic models have been described. This review aims to present the progress in development and validation of these prognostic models. A comprehensive literature review was performed to identify studies that proposed a new prognostic model in DLBCL. A total of 38 studies met the inclusion criteria. The IPI, revised IPI (R-IPI), and National Comprehensive Cancer Network (NCCN)-IPI were the most studied prognostic indexes, externally validated and commonly used to compare to other models. Despite an increasing number of prognostic models have been proposed lately, most of them lack external validation. Further studies, that combine biological and clinical markers with prognostic significance, are needed to determine the optimal prognostic tool for more personalized treatment approach to DLBCL patients.